The Effect Of Emotional Quotient And Adaptability On Performance Of The Tasikmalaya Health Office Employees - Nova Naufal; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2022)
Performance is the ability possessed by each individual in doing a job so that it becomes an achievement in achieving the goals shown in the behavior displayed. This study aims to determine the effect of emotional quotient and adaptability on the performance of the Tasikmalaya Health Office employees. The research method used in this study is a quantitative approach. The population in this study is civil servants and works at the Tasikmalaya Health Office. The sampling technique used in this study was census (saturated sampling), and the total sample was the entire population. Data was collected through questionnaires and interviews. The data analysis technique used is multiple linear regression analysis. To test the hypothesis, we used the F test and t test. The test results on the hypothesis show that together the variables of emotional quotient and adaptability have a positive and significant effect on improving the performance of the Tasikmalaya Health Service employees, and partially the emotional quotient and adaptability variables have a positive and significant effect on improving the performance of the Tasikmalaya Health Service employees.